A general self-powered wireless sensing solution based on triboelectric-discharge effect. (January 2023) - Wang, Haoyu; Xia, Xin; Fu, Jingjing; Li, Jianan; Chen, Chaojie; Dai, Yuan; Fan, Zhiyong; Hu, Guobiao; Zi, Yunlong
Abstract: With the rapid growth of the smart city, wireless sensors are highly preferred in plenty of application scenarios. To address the challenges of real-time sensing, power supply, and wireless signal transmission in current wireless sensors, a self-powered wireless sensing e-sticker (SWISE) based on the triboelectric-discharge effect has been proposed. However, the previously designed SWISE can only detect the unquantifiable signal of its own, which limited its applications. Herein, through studies about electromagnetic (EM) wave characteristics, we couple commercial sensors of different mechanics with EM wave generated by the triboelectric-discharge effect to realize a general self-powered wireless sensing solution for various physical signals. In addition, the integrated device is designed to combine with multiple sensors, with the characteristics of being thin and flexible. Based on this solution, a self-powered wireless temperature and pressure sensing system is demonstrated, with an error rate down to 0.18 %, and a multi-point sensing array was also realized for broad potential applications. This work proposes a self-powered wireless sensing platform that is compatible with various commercial sensors with different physical signals, which promises great potential for self-powered wireless sensing in the smart city and Internet of Things, such as robotic dynamic sensing, infrastructure monitoring, human-machine interface, etc. Graphical Abstract: ga1 Highlights: Theoretical model of triboelectric-discharge effect and EM-wave modulations was studied. The TDE-SWIS system was put forward to directly convert the mechanical signal input to modulated EM wave. The TDE-SWIS system offered an interface to commercial sensors to realize self-powered wireless sensing data transmission. The integrated TDE-SWIS device was thin, light, and flexible. Self-powered wireless temperature and pressure sensing system was demonstrated.